Historical Demographic Review of Industrial Cities of Tashkent Region - Allayerovich, Peremkulov Jamshid (International Journal of Psychosocial Rehabilitation, 2020)
There is no doubt that the direct involvement of such issues as urban population, its number, national composition, share in productionservesfor the increase of the value of research on the history of cities. However, the widespread use of modern research methods is of particular importance in the study of these principles and their correct interpretation. At the same time, especially in view of the socio-economic and political tasks aimed at preserving the independence of the Republic of Uzbekistan, its scientific substantiation is a requirement of today. This article is devoted to the study of urbanization processes in industrial cities of Tashkent region such as Angren, Chirchiq, Almalyk and Bekabad by highlighting the population migration and related demographic changes in this area. The periodic limit of the article is set from the second quarter of the XX century to the beginning of the XXI century. The article focuses on the migration of these resource cities during the years of Soviet rule, and then the changes that happened during the years of independence. In addition, economic, social and political factors influencing changes in population dynamics were revealed. The article also highlightes the contradictions and problems in the Soviet government’s concepts for the construction of industrial cities. It was argued that these problems had affected the development of cities during the years of independence. In addition, the role of the Second World War in the formation of resource cities in Uzbekistan is highlighted. The population dynamics in each region has studied separately and the general description of the cities of Tashkent region has been presented. At the same time, the policy pursued by the Soviet government was revealed through the focus on the ethnic composition of the population. It is noted that due to the economic, social and political reforms carried out by the republic during the years of independence, the urbanization process in the studied cities is stabilizing.